Scripted Misunderstandings and Humour: A Case Study of Monty Python’s Dialogues - Kavetska Alisa Anastasiia (Psychology of Language and Communication, 2025)
The major goal of this paper is to explore the pragmatic mechanisms underlying the interpretation of fabricated misunderstandings designed to generate humour. In order to show what is involved, the data selected from Monty Python’s productions are analysed. The relevance-theoretic tools (Sperber & Wilson, 1986/1995; Wilson & Sperber, 2012) are deployed to elucidate the pragmatic mechanisms at work. The analysis, based on five aspects of misunderstanding, reveals how engineered miscommunication might happen at either explicit or implicit level of meaning, involving different sources, and repair strategies, and how incongruity, essential to trigger humorous effect, is created as a result. The availability of contextual information, as well as other factors influencing (un)successful inferential outcomes are explored. It is also shown how weak communication, argued to contribute to the punchline effect (Jodłowiec, 2015; Piskorska & Jodłowiec, 2018; Jodłowiec & Piskorska 2024), is at work in processing film dialogues by the viewer.